(untitled) (Bangladesh Journal of Psychiatry, 2020)
Haematohidrosis is an uncommon disorder of unknown etiology that could be puzzling to physicians. Sufferers of this disorder were often adolescent females who were undergoing some stressful or emotional event; which might be associated with the activation of the sympathetic nervous system. These episodes involved spontaneous bleeding from skin and mucosal membranes without the involvement of trauma. An 11-years-old girl had admitted in a psychiatry hospital with recurrent episodes of bleeding from the eyes, nose and palm for one and a half years. She had been diagnosed with haematohidrosis following through clinical examination and laboratory investigations conducted a few months back prior to admission. However, the treatment appeared to be ineffective, perhaps owing to the patient’s comorbid attention deficit hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD). The patient was then treated with combined pharmacological and psychological interventions, thus bringing about an improvement in this challenging case. Bang J Psychiatry 2020; 34(2): 33-34